Decoupled kinematics of two neighbouring permafrost creeping landforms in the Eastern Italian Alps. Issue 13 (28th August 2019) - Seppi, Roberto; Carturan, Luca; Carton, Alberto; Zanoner, Thomas; Zumiani, Matteo; Cazorzi, Federico; Bertone, Aldo; Baroni, Carlo; Salvatore, Maria Cristina
Abstract: An overall acceleration of rock glacier displacement rates in the Alps has been observed in recent decades, with several cases of destabilization leading to potential geomorphological hazards. This behaviour has been attributed to the rising permafrost temperature, induced by atmospheric warming and regulated by thermo‐hydrological processes. Landforms derived from the interaction of glacier remnants and permafrost are widespread in mountain areas, but are less studied and monitored than talus rock glaciers. This work presents a comparative study of a talus rock glacier and a glacial‐permafrost composite landform (GPCL) in the Eastern Italian Alps. The two landforms are only 10 km apart, but have rather different elevation ranges and main slope aspects. The kinematics and ground thermal conditions were monitored from 2001 to 2015 along with geomorphological surveys, analyses of historical maps and remote sensing data. The dynamic behaviour of the rock glacier was similar to the majority of monitored rock glaciers in the Alps, with an acceleration after 2008 and a velocity peak in 2015. In contrast, the GPCL had a nearly unchanged displacement rate during the observation period. Statistical analyses of kinematic vs. nivo‐meteorological variables revealed a dynamic decoupling of the two landforms after 2008 that corresponds with increased winter snow accumulation. Although the kinematics of both landforms respond to ground surface temperature variations, the collected evidence suggests a different reaction of ground surface temperature to variations in the precipitation regime. This different reaction is likely due to local topo‐climatic conditions that affect snow redistribution by wind. The different reactions of the two systems to the same climatic forcing is likely a legacy of their different origins. GPCL dynamics result from interaction of permafrost and residual glacial dynamics that are associated with possible peculiarities in the internal/basal meltwater circulation, whose future response is uncertain and requires improved understanding. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : A comparative study of a talus rock glacier and a glacial‐permafrost composite landform from 2001 to 2015. The different dynamic reaction of the two landforms to the same climatic forcing is likely a legacy of their different origin. The rock glacier reacts like many rock glaciers in the Alps, with acceleration after 2008 and a velocity peak in 2015. The composite landform dynamics results from the interaction of periglacial and residual glacial dynamics.